Sub-systemic Effects of Power Dynamics in the International System: With Focus on the Great Powers’ Relations - Eshagh Sardarimehr; Mahmood Sariolghalam (رهیافتهای سیاسی و بین المللی)
The behavior and relations of great powers are among the most important variables playing a role in the systemic dynamics of the international system. The present article focuses on two levels of systemic and sub-systemic analyses of the international system. This study will examine the following hypothesis:  that in the international system where there are established and emerging great powers with considerable power discrepancy from other powers, economic, political, security and technological relations of all the other actors in the sub system with each great power depends on the relations and dynamics between the two great powers. The findings of this research demonstrate that the international system is in a redistributive state of power relations. In this context, relying on one or some theories in separate frameworks will not provide a proper understanding of the transition stage of current international politics. This research aims to achieve an eclectic theoretical model regarding the sub-systemic effects of the international system dynamics by juxtaposing the presumptions of neo-realism and neo-liberalism paradigms while drawing on the systems theory and subordinate systems.